209k views
3 votes
Simplify
Y exponent -5/ y exponent -4

Simplify Y exponent -5/ y exponent -4-example-1

2 Answers

5 votes

Answer:


(1)/(y)

Explanation:

using the rule of exponents


(a^(m) )/(a^(n) ) =
a^((m-n))


a^(-m) =
(1)/(a^(m) )

given


(y^(-5) )/(y^(-4) )

=
y^((-5-(-4)))

=
y^((-5+4))

=
y^(-1)

=
(1)/(y)

User Verhie
by
4.8k points
2 votes

Answer:

"Simplify" is an instruction to rewrite the expression with as few symbols as possible. 5y-4 and 5/y4 have the same number of symbols.

A possible alternative direction might have been to rewrite without the negative exponent.

User Kersten
by
5.0k points